Effects of aerobic fitness on oxygen uptake kinetics in heavy intensity swimming - Reis, J. F.; Alves, F. B.; Bruno, P. M.; Vleck, V.; Millet, G. P. (European Journal of Applied Physiology, 2012)
This study aimed to characterise both the V O2 kinetics within constant heavy-intensity swimming exercise, and to assess the relationships between VO2kinetics and other parameters of aerobic fitness, in well-trained swimmers. On separate days, 21 male swimmers completed: (1) an incremental swimming test to determine their maximal oxygen uptake ð VO2maxÞ, first ventilatory threshold (VT), and the velocity associated with VO2max ðv VO2maxÞ and (2) two square-wave transitions from rest to heavy-intensity exercise, to determine their VO2kinetics. All the tests involved breath-by-breath analysis of freestyle swimming using a swimming snorkel. _VO2kinetics was modelled with two exponential functions. The mean values for the incremental test were 56.0 ± 6.0 ml/minkg, 1.45 ± 0.08 m/s; and 42.1 ± 5.7 ml/min kg for VO2max, v VO2 max and VT, respectively. For the square-wave transition, the time constant of the primary phase (sp) averaged 17.3 ± 5.4 s and the relevant slow component (A0 sc) averaged 4.8 ± 2.9 ml/min kg [representing 8.9% of the end-exercise VO2(%A0 sc)]. sp was correlated with v VO2max (r = -0.55, P = 0.01), but not with either VO2max (r = 0.05, ns) or VT (r = 0.14, ns). The %A0 sc did not correlate with either V O2max (r = -0.14, ns) or v VO2max (r = 0.06, ns), but was inversely related with VT (r = -0.61, P\0.01). This study was the first to describe the VO2 kinetics in heavy-intensity swimming using specific swimming exercise and appropriate methods. As has been demonstrated in cycling, faster VO2kinetics allow higher aerobic power outputs to be attained. The slow component seems to be reduced in swimmers with higher ventilatory thresholds.